The Fall of the Ottomans : The Great War in the Middle East, 1914-1920 - Rogan, Eugene (London Allen Lane, 2015)
For some four centuries the Ottoman Empire had been one of the most powerful states in Europe as well as ruler of the Middle East.
Include Notes, Bibliography and Index
Keywords: World War, 1914-1918 - Campaigns - Middle East -- World War, 1914-1918 -Turkey